Improving The Civic Disposition In An Effort To Improve Pride In One’s Own Nation - Purwita, Nurul (Jurnal Pendidikan Ilmu Sosial, 2021)
This writing aims to identify, understand, and examine the causes and solutions of the low pride in the nation and state itself, namely Indonesia. The method used in writing is a qualitative method of document or text study with factual data obtained from reliable sources. The results obtained from this writing, the writer knows that the cause of the lack of a sense of nationalism in the nation and state, one of them is due to the flow of globalization that is difficult to stem and less optimal character education. Thus, it can be concluded that various factors influence the low level of pride in the nation and the state itself. So those efforts are needed to overcome these problems, one of which is efforts to improve character education based on civic disposition.